"Hai...It's Me, I Am Your Fanboy" : Self-Representation Fanboy K-Pop on Instagram - Kusnul Fitria; Budi Irawanto; Wiwik Sushartami (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aimed to explore the self-representation of K-Pop fanboys on Instagram by using a qualitative approach with digital ethnography and content analysis methods. Data was collected by investigated the self-representation of K-Pop fanboy Instagram accounts. The results showed that their self-representation involved a complex set of strategies, both visual and collaborative. By examining via the photos, videos and collaborations with some various parties, K-Pop fanboys creatively presented their identity as K-Pop fans. This representation is consciously constructed as an authentic expression of identity, reflecting a unique self-image rather than a mere imitation. Moreover, their creative activities demonstrated an active role in producing new meanings, these were not only as consumers of popular culture but also as contributors in the fandom community. This research provided an in-depth understanding of the dynamics of self-representation in the digital age as well as the role of social media in fan identity construction.